An examination of the relationships between the transfer of information and communications technologies and capacity building towards sustainable development of small and medium enterprises : a focus on Rwanda and Tanzania - Amadi-Echendu, J.E. (Joe) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2016.